A assistência social e o trabalho com as pessoas em situação de rua no CREAS: um campo de intercessão - Souza, William Azevedo [UNESP] (2015)
We will explain our praxis of Intercessão-Research on the work with homeless people at the Social Assistance Specialized Reference Center (CREAS). We will discuss the social assistance field under the worker-intercessor-researcher sight that uses the following references: Psychoanalysis on Freud and Lacan field, Historical Materialism, Institutional Analysis and the Philosophy of Difference. Those references enhable to analyse and to act in response to the practices, knowledges and discourses on this field. We will concept Social Assistance as an institution, and will go on a brief path through the Social Assistance National Policy and the context that gave origin to it, taking some considerations about this process. Following that, we will paradigmatic analyse Social Assistance as two paradigms, considered both alternative and contradictory: Charity Philanthropy Assistentialist Paradigm (PCFA), which holds hegemony on the Social Assistance fields, and the Subject of Rights Paradigm (PSD), this as a work horizon that goes on the direction of the assisted population's and the own Social Assistance worker's interests. Also will be explained the Intercessor Device's basis: an Intercessão-Research tool, intending to act in the service's provider public institution's praxis. Ruled on those elements, our praxis as a worker-intercessor will be reported, or better saying, the crossings, events and daily attendances with the homeless people; in a large city which is in the implantation process of the specialized services: social approach and attendance to the homeless people